2020
DOI: 10.3892/mmr.2020.11293
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Bailing capsules in the treatment of lupus nephritis: A meta‑analysis

Abstract: Previous studies have explored the treatment of lupus nephritis with Bailing capsules; however, due to limited sample sizes and inconsistent results across these studies, no definitive conclusions have been drawn. Thus, the present study aimed to provide evidence for the effectiveness of Bailing capsules in the treatment of lupus nephritis. To obtain relevant clinical studies (published before 20 July 2019), PubMed, embase, cochrane library, china national Knowledge infrastructure, WanFang and the chinese Biom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…Previous studies have focused on the effect of TAC combined with other drugs [ 16 , 17 ], but did not evaluate the effect of the combination on blood TAC concentration. Our study showed that the combination of Bailing and Huangkui with TAC affects blood TAC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on the effect of TAC combined with other drugs [ 16 , 17 ], but did not evaluate the effect of the combination on blood TAC concentration. Our study showed that the combination of Bailing and Huangkui with TAC affects blood TAC concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Several semi-synthetic derivatives of artemisinin with greater solubility or bioactivity, such as dihydroartemisinin, artemether, and arteether, artesunate have been developed and investigated in several research works [140,141]. Along with its anti-malarial effect, artemisinin and its derivatives have exhibited anti-inflammatory, immunoregulatory, and antioxidant properties [142]. Like some other conventional anti-malarial drugs, including chloroquine and hydroxychloroquine, artemisinin derivatives are assumed to have beneficial therapeutic effects on SLE [143,144].…”
Section: Purified Molecules From Natural Sourcesmentioning
confidence: 99%
“…In the TCM theory, C. sinensis has the functions of invigorating the kidneys, improving lung function, and enhancing the original qi . It has been suggested that C. sinensis regulates the immune system bidirectionally, reduces tubulointerstitial damage, inhibits renal fibrosis, and improves renal functions ( Barido et al, 2020 ; Li et al, 2020 ). In six randomized controlled trials with treatment duration of 2–12 months, the effects of C. sinensis were tested on a total of 507 LN patients ( Li et al, 2006 ; Davidson et al, 2019 ; Ren et al, 2019 ; Yu et al, 2021b ).…”
Section: Traditional Chinese Medicine Monomers In Lupus Nephritismentioning
confidence: 99%